Isolated third cranial nerve palsy as the presenting sign of tuberculum sellae meningioma: a case report - Alotaibi, Azizah; Althunayyan, Fay; Alshehri, Shuroq; Al-Jehani, Hosam (Frontiers in Ophthalmology, 2025)
Tuberculum sellae meningioma (TSM) is an uncommon tumor among all intracranial meningiomas. As these tumors grow, they compress the surrounding structures, including the optic nerves and the pituitary gland. Ocular motor nerve palsy (OMNP) can occur as an isolated mononeuropathy or as part of multiple cranial nerve palsies. The role of corticosteroids in the management of OMNP has not been fully studied in the literature. In this report, we present a case of a previously well middle-aged woman who presented with severe headache and isolated OMNP on examination. MRI of the brain showed a small TSM that extends into the right optic canal. In our case, we noted the expedient and complete recovery of isolated OMNP within a few days following treatment with dexamethasone. This case report is on an isolated OMNP associated with TSM, which has not been previously reported. In addition, it highlights the role of corticosteroids in achieving rapid recovery from OMNP.